2022
DOI: 10.3389/fpsyg.2022.894195
|View full text |Cite
|
Sign up to set email alerts
|

How Does Media Use Promote the Purchase of Private Medical Insurance? A Moderated Mediation Model

Abstract: Various information media (such as TV and the Internet) have become the main channels through which for people to obtain information. Previous studies showed that media use influences the purchase of private medical insurance; however, research on its internal influence mechanism is still relatively weak. Using data from the Chinese General Social Survey 2017, this study constructed a moderated mediation model to analyze the mechanism of the influence of media use on the purchase of private medical insurance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…These studies are limited to the influence of personal endowments (47), intergenerational support, social security (51), and other factors (56) on the choice of old-age support pattern, and do not examine internet use. Shi Hao et al conducted a study on the relationship between media use and commercial insurance and found that using the internet can promote the purchase of commercial insurance (57). But the commercial insurance here is commercial medical insurance and not include commercial pension insurance.…”
Section: Discussionmentioning
confidence: 99%
“…These studies are limited to the influence of personal endowments (47), intergenerational support, social security (51), and other factors (56) on the choice of old-age support pattern, and do not examine internet use. Shi Hao et al conducted a study on the relationship between media use and commercial insurance and found that using the internet can promote the purchase of commercial insurance (57). But the commercial insurance here is commercial medical insurance and not include commercial pension insurance.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, the most effective methods of public health education are face-to-face public health education and Internet public health education ( 11 ). They also suggest that the use of the Internet can effectively promote the purchase of commercial health insurance ( 48 ). A comprehensive health education score (Public health education) was constructed using the entropy value method to measure public health education in each region.…”
Section: Methodsmentioning
confidence: 99%
“…Students’ SRHS was not improved by enrollment in a unified school-based private health insurance plan although individualized health insurance significantly improved students’ SRHS [ 15 ]. Media promotion had a positive effect on purchasing private medical insurance, whereas personal awareness had a negative effect [ 16 ]. The second approach involves exploring the impact of ‘place’ on health from a broader perspective than the individual (e.g., focusing on the community, city, or province).…”
Section: Introductionmentioning
confidence: 99%